The Appearance of False Sign in Ads at Social Media - Ilhamsyah, Ilhamsyah; Herlina, Herlina (Academic Journal Perspective: Education, Language, and Literature, 2018)
The aim of this study is to determine the presence of signs and combinations of signs (codes) that are present on the fictitious figure of Sarah Aprilia in Cologne Bask advertisingÂ onÂ theÂ internet.Â TheÂ signÂ andÂ theÂ codeÂ inÂ generalÂ shouldÂ haveÂ aÂ common understanding by prospective readers (target audience). This research used qualitative approachÂ withÂ interpretativeÂ descriptiveÂ methodÂ becauseÂ semioticÂ scienceÂ isÂ digging and discovery the meaning. In analyzing the fictitious figure of Sarah Aprilia, the sign thatÂ appearanceÂ isÂ falseÂ sign.Â DeceptiveÂ markÂ isÂ aÂ signÂ thatÂ unknownÂ originÂ ,Â butÂ the engineering rests on a natural object (hybrid), but viewers assume it was real presence. This is due to the many cross signs presented visual codes that make the figure of Sarah Aprilia as a real figure.